A Plasmid With Conserved Phage Genes Helps Klebsiella pneumoniae Defend Against the Invasion of Transferable DNA Elements at the Cost of Reduced Virulence - Cai, Mufeng; Pu, Bingchun; Wang, Yue; Lv, Lin; Jiang, Chunyu; Fu, Xiaomei; Zhang, Yan; Zhao, Wei; Dong, Ke; Yang, Yi; Liu, Yangming; Wei, Yalu; et al. (Frontiers in Microbiology, 2022)
Klebsiella pneumoniae exhibits extensive phenotypic and genetic diversity. Higher plasmid loads in the cell were supposed to play an important role in its genome diversity. Although some plasmids are widely distributed in Kp populations, they are poorly recognized. A plasmid named p2 in strain Kp1604 was predicted to be an intact prophage similar to Salmonella phage SSU5. However, our study showed that p2 was specifically packaged into membrane vesicles (MVs) rather than phage particles triggered by mitomycin C and subinhibitory concentrations of antibiotics. p2-minus mutant Kp1604Δp2 did not affect MV production. Compared with Kp1604, the capacity of plasmid uptake and the amount of phage burst of Kp1604Δp2 were improved. Moreover, virulence of Kp1604Δp2 also increased. Our results indicated that p2 could contribute to the host defense against the invasion of transferable DNA elements at the cost of reduced virulence. Further study on the mechanism will help us understand how it provides adaptive phenotypes to host evolution.